Assessment process in dental schools: perspectives and teaching challenges - Verydianna Frota CARNEIRO; Alice Maria Correia PEQUENO; Maria de Fátima Antero Sousa MACHADO; Dulce Maria de Lucena AGUIAR; Cleide CARNEIRO; Rithianne Frota CARNEIRO (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Objective: To analyze the teachers' view on the difficulties and the contribution of the assessment process to an undergraduate program in dentistry at a university in Fortaleza, Ceará Methods: This is a descriptive research with a qualitative approach. Research subjects were undergraduate dentistry professors with teaching experience in such program of five years or more. Data collection was carried out from September to October 2014, through a documentary analysis of, among others, the pedagogical political project and a semi-structured interview. A thematic review was adopted to interpret data Results: The main difficulty in the assessment was quantifying the student's performance. The influence of the assessment on professional education depends on the understanding of the assessment process and the acquired experience. Teachers recognize the punishing and pushing effect that still remain in such process and requires a major change Conclusion: Teachers should establish assessment criteria guided by their teaching goals, without forgetting the profile of graduates from their institutions. Besides, assessment should encourage learning by coping with unfavorable emotions, restoring confidence and the learning ability. The course should be based on a curricular pedagogical project supported by guiding principles, in order to drive the assessment practice and avoid any seclusion.